Knowledge and attitude toward the management of pre-eclampsia and eclampsia among healthcare providers working in maternity settings in Jordan: A cross-sectional study - Al-Tarawneh, Tamador R.; Bdeir, Roba; Al-ja’freh, Sarah; Jakalat, Suad; Al-Qaaneh, Ayman M.; Sumaqa, Yasmeen Abu (Belitung Nursing Journal, 2025)
Background: Pre-eclampsia and eclampsia remain major causes of maternal morbidity and mortality. Healthcare providers’ knowledge and attitudes are critical for effective management. Objective: This study aimed to assess healthcare providers’ knowledge and attitudes regarding the management of pre-eclampsia and eclampsia in Jordan. Methods: A cross-sectional study was conducted from September to October 2024 among 147 healthcare providers from seven public hospitals across three regions in Jordan. Data were collected via a structured questionnaire and analyzed using descriptive statistics, bivariate tests, and multivariate logistic regression. Results: Overall, 88% demonstrated adequate knowledge of pre-eclampsia, and 83% demonstrated adequate knowledge of eclampsia. In bivariate analysis, knowledge was associated with educational program and training attendance. However, after adjusting for other variables in the multivariate model, only education and gender remained significant, while training was no longer associated with knowledge. For attitudes, 78% had a positive attitude. Although gender and education were associated with attitudes in bivariate analyses, these associations did not remain statistically significant in the multivariate model. Conclusion: Healthcare providers showed generally adequate knowledge and predominantly positive attitudes toward managing pre-eclampsia and eclampsia. Higher educational attainment independently predicted knowledge, while no independent predictors of attitude were identified. The study highlighted the need for continuous, focused educational training programs, particularly for nurses and midwives. The modest sample size and focus on public hospitals should be considered when interpreting the results.